A Review of Adaptive Mechanisms in Fish Retinal Structure and Opsins Under Light Environment Regulation - Zheng Zhang; Fan Fei; Liang Wang; Yunsong Rao; Wenyang Li; Xiaoqiang Gao; Ao Li; Baoliang Liu (Fishes, 2026)
Light, as one of the most crucial environmental factors, plays an essential role in the growth, physiology, and evolutionary survival of fish. To cope with diverse light conditions in aquatic environments, fish adapt through photosensory systems composed of both visual and non-visual pathways. The retina is a key component of the visual system of fish, capable of converting external optical signals into neural electrical signals, making it crucial for visual formation. During the process of visual signal transduction, opsins serve as the molecular foundation for vision formation. They can be divided into two major categories: visual opsins and non-visual opsins. Among these, melanopsin, as a member of the non-visual opsin family, acts as a key upstream factor in the circadian phototransduction pathway of fish. In this review, we review the adaptability of fish retinal structures to light reception and introduce in detail the gene diversity and relative expression levels of fish opsins. At the same time, we comprehensively describe the molecular mechanism by which fish adapt to changes in the underwater light environment. We also concluded that melanopsin, as a non-imaging photoreceptor, possesses not only core light-sensing functions but also non-imaging visual functions such as circadian rhythm regulation, body coloration changes, and hormone secretion. This review suggests that future research should not only elucidate the physiological functions of melanopsin in fish but also comprehensively reveal the mechanisms underlying the multi-adaptive nature of fish vision across varying light environments. Through these studies, researchers can have a deeper understanding of the physiological regulation mechanism of fish in complex light environments, and then formulate fish light environment management strategies, optimize aquaculture practices, improve economic returns, and promote the development of related fields.